2018
DOI: 10.1016/j.rcpeng.2017.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, self-esteem and body image in girls with precocious puberty

Abstract: Currently, the age of onset for pubertal changes is decreasing, especially in girls, which may have an impact on psychosocial factors such as anxiety, self-esteem and body image. The aim of the present study is to compare these variables in two groups: a group of 15 girls with precocious puberty and a group of 16 girls of the same age without precocious puberty. A non-experimental descriptive design was used and the State-Trait Anxiety Inventory for Children (STAIC) and Self-Description Questionnaire (SDQ) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…In children, however, such complications are rare. Conversely, epilepsy often occurs as a complication of autism spectrum disorder (ASD) or an intellectual impairment 12 and depression and anxiety are common in children with ASD and attention-deficit/hyperactivity disorder (ADHD). 13,14 In this study, children with a diagnosis of both epilepsy and developmental disorders were classified into epilepsy and children with developmental disorders alone showed the fourth highest total QTA30 scores among those in the regular visit group.…”
Section: Discussionmentioning
confidence: 99%
“…In children, however, such complications are rare. Conversely, epilepsy often occurs as a complication of autism spectrum disorder (ASD) or an intellectual impairment 12 and depression and anxiety are common in children with ASD and attention-deficit/hyperactivity disorder (ADHD). 13,14 In this study, children with a diagnosis of both epilepsy and developmental disorders were classified into epilepsy and children with developmental disorders alone showed the fourth highest total QTA30 scores among those in the regular visit group.…”
Section: Discussionmentioning
confidence: 99%
“…Precocious puberty has been associated with increased delinquency and physical aggression, and females with early puberty have been suggested to face greater social isolation and bullying than their peers [ 18 , 19 ]. Some studies have shown increased stress and anxiety in females with precocious puberty [ 20 , 21 ]. These data on time interval to menarche after GnRHa treatment and clinical factors that influence this time interval can aid clinicians in counseling parents and reduce some of the parental and patient concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Puberte prekoksta beden imajı olumsuz etkilenmektedir. Erken pubertal zamanlama kız çocukları için beden imajı ve cinsiyet rol beklentileri üzerinde olumsuz bir etki ortaya çıkarabilir (17).…”
Section: Puberte Prekoks'un Kız çOcuklar üZerine Etkileriunclassified
“…Erken pubertal gelişimin sonucu stres, anksiyete ve depresyonun arttığını gösteren yayınlar bulunmaktadır (9,17,24). Yapılan bir çalışmada bu gelişimsel dönemde kızların daha yüksek sosyal kaygı düzeyine sahip oldukları, daha saldırgan, olumsuz akran etkilerine daha yatkın, daha fazla suça eğilimli oldukları, ancak yaş ilerledikçe bu etkinin azaldığı sonucuna ulaşılmıştır (8,25).…”
unclassified